LAW ENFORCEMENT ON CRIMINAL ACTIONS OF LENDING CORRUPTION IN PT. MALUKU BANK (Judgment Study at Ambon District Court) - Jafarudin; Hambali Thalib; Nur Fadhillah M (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal